1997
DOI: 10.1051/kmae/1997055
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of the white-clawed crayfishAustropotamobius pallipes: The usefulness of the mitochondrial DNA marker

Abstract: The white-clawed crayfish, Austropotamobius pallipes pallipes, still has a wide-spread distribution in France, but since the last century, populations have declined because of habitat alteration (due to human disturbance) and have been also eliminated by crayfish plague, for which introduced exotic species are a vector. Action plans for the conservation of A. pallipes are urgent and if recovery programmes are to be initiated in France, then it is important to estimate how much genetic variation is partitioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…SANTUCCI et al (1997) using electrophoretic techniques detected three population groups corresponding to A. torrentium, A. pallipes and A. italicus from various parts of Europe, but did not confirm A. lusitanicus as being a separate species. SOUTY-GROSSET et al (1997 and GRANDJEAN et al (2001a), however, using molecular markers, confirmed the subspecific status of A. p. pallipes, A. p. italicus and A. p. lusitanicus. Using morphological, electrophoretic and molecular techniques, LÖRTSCHER et al (1997) andLARGIADÈR et al (2000) confirmed BOTT's (1972) Austropotamobius berndhauseri for southern Switzerland.…”
Section: Taxonomymentioning
confidence: 76%
See 1 more Smart Citation
“…SANTUCCI et al (1997) using electrophoretic techniques detected three population groups corresponding to A. torrentium, A. pallipes and A. italicus from various parts of Europe, but did not confirm A. lusitanicus as being a separate species. SOUTY-GROSSET et al (1997 and GRANDJEAN et al (2001a), however, using molecular markers, confirmed the subspecific status of A. p. pallipes, A. p. italicus and A. p. lusitanicus. Using morphological, electrophoretic and molecular techniques, LÖRTSCHER et al (1997) andLARGIADÈR et al (2000) confirmed BOTT's (1972) Austropotamobius berndhauseri for southern Switzerland.…”
Section: Taxonomymentioning
confidence: 76%
“…There is some genetic evidence for this viewpoint (e.g. SANTUCCI et al, 1997;SOUTY-GROSSET et al, 1997;GRANDJEAN and SOUTY-GROSSET, 2000;GRANDJEAN et al, 2001b).…”
Section: Post-glacial Dispersal Of Crayfish In Europementioning
confidence: 99%
“…In order to define efficient conservation strategies, accurate data on systematics and population structure are crucial (SOUTY-GROSSET et al, 1997, SOUTY-GROSSET, GRANDJEAN andGOUIN, 2003). Although A. pallipes populations were shown to display great degrees of morphological and genetic diversity in the Alpine region (LARGIADÈR et al, 2000;LÖRTSCHER et al, 1997;SANTUCCI et al, 1997), nothing is known about the phylogenetic status and genetic composition of crayfish populations in South Tyrol.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade molecular techniques revealing a higher degree of variability have been developed and applied successfully in population studies of freshwater crayfish. Genetic differentiation of populations had been assessed using mitochondrial DNA (SOUTY-GROSSET et al, 1997;LARGIADER et al, 2000), RAPD-PCR (MACARANAS et al, 1995;SCHULZ, 2000;GOUIN et al, 2001), AFLP (FETZNER and CRANDALL, 1999) and microsatellites (GOUIN et al, 2000;EDSMAN et al, 2002;GOUIN et al, 2002). Phylogenetic studies MUNASINGHE et al, 2003), and reconstruction of the phylogeography were possible using mitochondrial DNA.…”
Section: Introductionmentioning
confidence: 99%